Transcriptome analysis reveals the promoting effects of exogenous melatonin on the selenium uptake in grape under selenium stress - Wang, Jin; Lu, Yuhang; Xing, Shanshan; Yang, Jinman; Liu, Lei; Huang, Kewen; Liang, Dong; Xia, Hui; Zhang, Xiaoli; Lv, Xiulan; Lin, Lijin (Frontiers in Plant Science, 2024)
Exogenous melatonin (MT) can promote horticultural crops growth under stress conditions. In this study, the effects of exogenous MT on the accumulation of selenium (Se) in grape were studied under Se stress. Under Se stress, exogenous MT increased the biomass, content of photosynthetic pigments and antioxidant enzyme activity of grapevines. Compared with Se treatment, MT increased the root biomass, shoot biomass, chlorophyll a content, chlorophyll b content, carotenoids, superoxide dismutase activity, and peroxidase activity by 18.11%, 7.71%, 25.70%, 25.00%, 25.93%, 5.73%, and 9.41%, respectively. Additionally, MT increased the contents of gibberellin, auxin, and MT in grapevines under Se stress, while it decreased the content of abscisic acid. MT increased the contents of total Se, organic Se and inorganic Se in grapevines. Compared with Se treatment, MT increased the contents of total Se in the roots and shoots by 48.82% and 135.66%, respectively. A transcriptome sequencing analysis revealed that MT primarily regulated the cellular, metabolic, and bioregulatory processes of grapevine under Se stress, and the differentially expressed genes (DEGs) were primarily enriched in pathways, such as aminoacyl-tRNA biosynthesis, spliceosome, and flavonoid biosynthesis. These involved nine DEGs and nine metabolic pathways in total. Moreover, a field experiment showed that MT increased the content of Se in grapes and improved their quality.Therefore, MT can alleviate the stress of Se in grapevines and promote their growth and the 删除的内容: 11 accumulation of Se.